Femoral neck fractures: can the type of synthesis reduce the causes of failure? - Berti, Matteo; Comitini, Saverio; Castiello, Emanuela; Mobilia, Giuseppe; Moghnie, Alessandro; Tigani, Domenico S. (Lo Scalpello - Journal, 2022)
Femoral neck fractures (FNFs) are one of the most common traumatic fractures. Although a considerable number of implants are available, there is no agreement on the most suitable technique, and complication rates are still unacceptably high. In this article, the main internal fixation implants for FNFs were considered to determine whether, in the literature, a relationship between the type of synthesis used and the risk of failure is present. The variable results reported in literature make it unreasonable to absolutely prefer one implant or construct, although some characteristics of the fracture and patient can guide the choice.